2015
DOI: 10.1186/s13024-015-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

The N17 domain mitigates nuclear toxicity in a novel zebrafish Huntington’s disease model

Abstract: BackgroundAlthough the genetic cause for Huntington’s disease (HD) has been known for over 20 years, the mechanisms that cause the neurotoxicity and behavioral symptoms of this disease are not well understood. One hypothesis is that N-terminal fragments of the HTT protein are the causative agents in HD and that peptide sequences adjacent to the poly-glutamine (Q) repeats modify its toxicity. Here we test the function of the N-terminal 17 amino acids (N17) in the context of the exon 1 fragment of HTT in a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 66 publications
3
31
1
1
Order By: Relevance
“…Recent in vivo studies from Yang and coworkers showed that a ∆N17 variant of huntingtin, which lacks the N17 module, leads to faithful reproduction of HD phenotypes in transgenic mice (56,57). In light of these observations, and given the relative ease of synthesis and purification of Htt-NTFs that lack the N17 module (19), we used constructs of the form Q n -C38 for a majority of our in vitro experiments.…”
Section: Constructs For In Vitro Experimentsmentioning
confidence: 99%
“…Recent in vivo studies from Yang and coworkers showed that a ∆N17 variant of huntingtin, which lacks the N17 module, leads to faithful reproduction of HD phenotypes in transgenic mice (56,57). In light of these observations, and given the relative ease of synthesis and purification of Htt-NTFs that lack the N17 module (19), we used constructs of the form Q n -C38 for a majority of our in vitro experiments.…”
Section: Constructs For In Vitro Experimentsmentioning
confidence: 99%
“…Addition of free N17 was found to accelerate aggregation of 51Q although later reports failed to reproduce these results . Interestingly, the deletion of N17 domain was found to accelerate aggregation of the polyQ domain in transgenic animal models . One possible explanation is the loss of NES (nuclear export signal) sequence which is localized in this domain, leading to the formation of more toxic intranuclear aggregates and explaining the contradictory results observed in vivo .…”
Section: Discussionmentioning
confidence: 95%
“…Addition of free N17 was found to accelerate aggregation of 51Q [26] although later reports failed to reproduce these results [47,60]. Interestingly, the deletion of N17 domain was found to accelerate aggregation of the polyQ domain in transgenic animal models [48,49]. One possible Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish has been used to model several neurodegenerative disorders due to its genetic conservation to mammals and ease of experimental manipulation [8]. In the context of HD, 1/11 transgenic zebrafish expressing mutant HTT exon 1 fragment exhibit adult-onset movement deficit, which is worsened by the deletion of the N-terminal first 17 amino acids (N17) of mutant HTT fragment [9]. To understand the functions of HTT in development, several studies in zebrafish have utilized antisense morpholinos to knock down HTT transcripts.…”
Section: Introductionmentioning
confidence: 99%